Editorial dossier “Criminal Procedure Systems and Judicial Impartiality”: Impartiality and evidence in criminal procedure – consequences to judge’s evidence power - Lorena Bachmaier Winter (Revista Brasileira de Direito Processual Penal)
The aim of this paper is to clarify the relationship between the principle of impartiality and the role of the judge in the trial with regard to the evidence. In particular I will argue that recognizing certain powers to the judge to intervene in the cross-examination of witnesses or interrogating the defendant, does not necessarily undermine the fundamental right to an impartial judge. It will be analyzed if the principle of impartiality does per se justify a completely passive role of the trial judge, or rather a position of the judge as mere spectator is a requirement of a certain understanding of the adversarial model. To this end, I will first address the concept of impartiality and its various meanings.